2015
DOI: 10.1016/j.immuni.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

The Virome in Host Health and Disease

Abstract: The mammalian virome includes diverse commensal and pathogenic viruses that evoke a broad range of immune responses from the host. Sustained viral immunomodulation is implicated in a variety of inflammatory diseases, but also confers unexpected benefits to the host. These outcomes of viral infections are often dependent on host genotype. Moreover, it is becoming clear that the virome is part of a dynamic network of microorganisms that inhabit the body. Therefore, viruses can be viewed as a component of the mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
149
0
15

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(165 citation statements)
references
References 100 publications
1
149
0
15
Order By: Relevance
“…Though viruses have commonly been conceived as harmful, recent research has shown that many of them are neutral (not affecting host fitness) or even mutualistic (increasing host fitness) (Bao & Roossinck, 2013;Cadwell, 2015aCadwell, , 2015bDennehy, 2014;Foxman & Iwasaki, 2011;MacDuff et al, 2015;Roossinck, 2008Roossinck, , 2011Roossinck, , 2015Ryan, 2009;Shen, 2009;Stoltz & Whitfield, 2009;Virgin, 2014a). Here I focus on the case of mutualistic viruses.…”
Section: Mutualistic Virusesmentioning
confidence: 99%
See 3 more Smart Citations
“…Though viruses have commonly been conceived as harmful, recent research has shown that many of them are neutral (not affecting host fitness) or even mutualistic (increasing host fitness) (Bao & Roossinck, 2013;Cadwell, 2015aCadwell, , 2015bDennehy, 2014;Foxman & Iwasaki, 2011;MacDuff et al, 2015;Roossinck, 2008Roossinck, , 2011Roossinck, , 2015Ryan, 2009;Shen, 2009;Stoltz & Whitfield, 2009;Virgin, 2014a). Here I focus on the case of mutualistic viruses.…”
Section: Mutualistic Virusesmentioning
confidence: 99%
“…An increasing number of biologists have started to study the "virobiota" (all the viruses that live in or on a host) and the "virome" (the set of all the genes of the virobiota), as a potentially crucial part of the "microbiota" and "microbiome" 4 , respectively ((Reyes et al, 2010); (Moon & Stappenbeck, 2012); (Duerkop & Hooper, 2013); (Virgin, 2014b); (Cadwell, 2015b)). The human virobiota is made of both bacteriophages (i.e., viruses of bacteria) 5 , and eukaryotic viruses (Virgin, 2014b).…”
Section: Mutualistic Virusesmentioning
confidence: 99%
See 2 more Smart Citations
“…В его состав входят возбудители разных типов инфекций и вирусы, способные интег-рироваться в геном человека (например, эндогенные ретровирусы) или прокариот. Новые методы секвени-рования дают основание полагать о существовании множества ранее неизвестных вирусов эукариот [10].…”
Section: Introductionunclassified